Nutritional Profile, Proximate Composition and Health Benefits of Colocasia esculenta Leaves: An Underutilized Leafy Vegetable in Nigeria - Azubuike, N.C.; Maduakor, U.C.; Ikele, I.T.; Onwukwe, O.S.; Onyemelukwe, A.O.; Nwanjiobi, D.U.; Chukwu, I.J.; Achukwu, P.U. (Pakistan Journal of Nutrition, 2018)
Background and Objectives: Colocasia esculenta L. Schott, commonly known as Cocoyam, is commonly grown for its edible tubers but the leaves have been underutilized. This study was conducted to compare the proximate and mineral values of fresh, sun-dried and boiled C. esculenta leaves collected in Enugu State, Nigeria. Methodology: Proximate analysis was performed according to the standard AOAC methods while the mineral content was determined using atomic absorption spectrometry. The effect of no treatment, sun-drying and boiling of the leaves were investigated. Results: Proximate analysis showed that the sun dried leaves had higher carbohydrate, protein, fat and ash content than the fresh and boiled leaves. However, boiling decreased the ash, protein and fat contents of the leaves. Mineral content determination revealed that calcium, magnesium, potassium, sodium, iron and manganese contents were increased by sun drying whereas copper, phosphorus and zinc contents were decreased compared to the fresh leaves. Conclusion: This study revealed that sun-dried Colocasia esculenta leaves retained more of the nutrients than the fresh and boiled leaves. The leaves of C. esculenta may be a potential source of nutrients as leafy vegetables.